Identifikasi Faktor Penentu dan Perhitungan Standard Time Proses Washing di PT.X - Harry Setyawan Firmansyah; Nova Sepadyati (Jurnal Titra, 2020)
PT.X is a company engaged in the manufacturing of heat exchangers. PT.X has a standard time formula for each process on the production floor. The washing process formula currently only uses three variables from the specifications of each unit. The research carried out at PT.X aims to see whether the standard washing process standard time formula is still relevant or not to be used today. Observation data shows that the average time of 105.88% of the results of the calculation formula is greater than the actual time. The results of the calculation of the new formula are designed to approach the actual time and only use two of the seven factors that significantly influence the washing process time based on the ANOVA test results. The new standard time formula was built using a regression model. Standardizing the washing process using a new formula can reduce the washing process production costs by 39.8% from € 0.1008 / minute to € 0.0607 / minute.